A comparison between different concentrations and sources of cobalt in goat kid nutrition. (18th October 2016) - Dezfoulian, A. H.; Aliarabi, H.
Abstract : There have been extensive studies in sheep and cattle considering cobalt (Co) supplementation and its effects on vitamin B12 concentrations in the body. However, there are limited studies on goats. The aim of this study was to compare two different sources of Co (sulfate v . glucoheptonate) at two different concentrations (0.25 and 0.5 mg/kg dry matter) in goat kid nutrition, and to evaluate the effects of these supplements on performance, serum vitamin B12, blood biochemistry and rumen volatile fatty acids. For this purpose, 30 weaned male goat kids were randomly allotted to five treatments. Serum vitamin B12 increased during the trial in the Co-supplemented groups. Co supplementation increased serum glucose concentrations. On day 35, Co-supplemented groups had greater glucose concentrations compared with control. Propionic+iso-butyric acid concentrations increased only in the 0.5 mg Co glucoheptonate treatment ( P <0.05). Our results suggest that, despite the two sources of Co proving mostly similar, the main advantage of Co glucoheptonate compared with Co sulfate was in the ruminal synthesis of vitamin B12 . However, although providing Co at National Research Council recommendation levels maintained vitamin B12 above or at normal concentrations, Co supplementation of the Co sufficient basal diet increased vitamin B12 and glucose concentrations.